The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1037/pro0000174
|View full text |Cite
|
Sign up to set email alerts
|

In here and out there: Systemic alliance and intersession processes in psychotherapy.

Abstract: The processes clients engage in between therapy sessions (referred to as intersession processes; ISPs) are empirically supported as influential factor in psychotherapy. The current study examined the impact of the therapeutic alliance-both the individual alliance and the systemic alliance-on client engagement in ISP-thoughts, ISP-actions, and client perceptions of therapy progress. Eighty-one therapy clients provided responses regarding these therapy process variables, and results revealed that higher ratings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…ited size of primary studies (k ϭ 17), which may not accurately reflect the diverse universe of psychotherapy approaches; thus, an investigation of potential differential effects across particular treatment orientations was limited. Time-specific and outside-therapy confounds, for example, intersession processes, could have impact the results (see, e.g., Hartmann, Orlinsky, & Zeeck, 2011;Kaiser & Laireiter, 2019;Quirk, Smith, & Owen, 2018;Strunk et al, 2010). Based on our decision to include data sets where the alliance and symptoms were measured from Session 1 to 7 to predict posttreatment outcome, we cannot draw conclusions regarding later phases of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ited size of primary studies (k ϭ 17), which may not accurately reflect the diverse universe of psychotherapy approaches; thus, an investigation of potential differential effects across particular treatment orientations was limited. Time-specific and outside-therapy confounds, for example, intersession processes, could have impact the results (see, e.g., Hartmann, Orlinsky, & Zeeck, 2011;Kaiser & Laireiter, 2019;Quirk, Smith, & Owen, 2018;Strunk et al, 2010). Based on our decision to include data sets where the alliance and symptoms were measured from Session 1 to 7 to predict posttreatment outcome, we cannot draw conclusions regarding later phases of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are several questions raised, but not yet answered, by this investigation: A limitation of this meta-analysis is the relatively limited size of primary studies ( k = 17), which may not accurately reflect the diverse universe of psychotherapy approaches; thus, an investigation of potential differential effects across particular treatment orientations was limited. Time-specific and outside-therapy confounds, for example, intersession processes, could have impact the results (see, e.g., Hartmann, Orlinsky, & Zeeck, 2011; Kaiser & Laireiter, 2019; Quirk, Smith, & Owen, 2018; Strunk et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, recovery is partly dependent upon what and whom the patient has access to in the social world. The role of extra-therapeutic factors in therapy have long been acknowledged [57], and research shows how the alliance with the social network is more important than the patient-therapist alliance for the outcome [58]. Thus, the limited support for the efficacy of interventions aimed at BPD in adolescents, could then be understood as a result of that the fundamental structure of the current mental health systems is inadequate for the unique developmental and cultural needs of young people and that transformational change and service redesign is necessary.…”
Section: Mentalization-based Group Treatment For Adolescents With Bpd -Is It a Feasible Approach?mentioning
confidence: 99%
“…Previous studies on intersession activity showed that clients recalled the therapist and the therapeutic relationship to further work on problems in daily life, to seek comfort from negative emotions, and facilitate problem solving (Geller & Farber, 1993). Similarly, Owen et al (2012) and Quirk et al (2018) found that good alliance facilitated clients' engagement in more actions to address their issues in their daily life. The present study demonstrated that in affect-focused therapies such as AEDP and EFT, such carryover effects come from positive emotions sprung out from the relational experience with the therapist.…”
Section: In-session Cees and Postsession Changesmentioning
confidence: 97%